REAL-TIME DATA ANALYSIS IN THE CLOUD: A GOOGLE CLOUD STRATEGY UTILIZING GENAI - Vedaswaroop Meduri (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
The convergence of real-time data analytics, cloud computing, and Generative AI (GenAI) transforms how organizations process information and make decisions. This article explores the integration of GenAI with Google Cloud's real-time analytics capabilities, examining its impact on business operations and decision-making processes across various industries. By analyzing the implementation of these technologies in sectors such as finance, healthcare, and retail, we demonstrate how this integration enhances operational efficiency, improves predictive capabilities, and enables automated response systems. While organizations face challenges related to data privacy, model bias, and computational efficiency, the potential benefits in terms of operational improvements, cost reduction, and enhanced decision-making capabilities make this a crucial area for continued investment and development.